E. T. A. Hoffmann's Musical Writings: Kreisleriana, The Poet and the Composer, Music Criticism - Hoffmann, E. T. A. 1776-1822; Charlton, David; Clarke, Martyn (Cambridge Cambridge University Press, 1989)
This book contains the first complete translation in English of E. T. A. Hoffmann's major musical writings, complementing the well-known Tales. It offers, therefore, a long-awaited opportunity to assess the thought and influence of one of the most famous of all writers on music and the musical links with his fiction. Containing the first complete appearance in English of Kreisleriana, it reveals a masterpiece of imaginative writing whose title is familiar to musicians (from Robert Schumann's piano cycle) and whose profound humour and irony can now be fully appreciated. This volume offers translations aiming at the greatest fidelity to Hoffmann, as well as musical accuracy in the reviews. David Charlton's three introductory essays provide extensive information on the background to Romantic music criticism; on the origins and internal structure of Kreisleriana; and on Hoffmann and opera. A concluding essay by the late Friedrich Schnapp lists Hoffmann's planned reviews and those mistakenly attributed to him.
Keywords: Opera; Music criticism